ANALISIS SKALA USAHA DAN TINGKAT KEUNTUNGAN INDUSTRI KERAJINAN SONGKET DI KOTA PALEMBANG - Abu Kosim; Azwardi Azwardi (Jurnal Ekonomi Pembangunan, 2008)
This research is purposed to know the the production scale and  profit condition of songket industry in Palembang. By using The Constant Elasticity Supply, especially based on the value of homogenity h we can know the production scale is constant returns to scale and so the industrial profit is maximized.